Anandamide drives cell cycle progression through CB1 receptors in a rat model of synchronized liver regeneration. Issue 12 (24th August 2015) - Pisanti, Simona; Picardi, Paola; Pallottini, Valentina; Martini, Chiara; Petrosino, Stefania; Proto, Maria Chiara; Vitale, Mario; Laezza, Chiara; Gazzerro, Patrizia; Di Marzo, Vincenzo; Bifulco, Maurizio
<x xml:space="preserve">Abstract</x> The endocannabinoid system, through cannabinoid receptor signaling by endocannabinoids, is involved in a wide range of functions and physiopathological conditions. To date, very little is known concerning the role of the endocannabinoids in the control and regulation of cell proliferation. An anti‐proliferative action of CB1 signaling blockade in neurogenesis and angiogenesis argues in favor of proliferation‐promoting functions of endocannabinoids through CB1 receptors when pro‐growth signals are present. Furthermore, liver regeneration, a useful in vivo model of synchronized cell proliferation, is characterized by a peak of anandamide that elicits through CB1 receptor, the expression of critical mitosis genes. The aim of this study was to focus on the timing of endocannabinoid signaling changes during the different phases of the cell cycle, exploiting the rat liver regeneration model following partial hepatectomy, the most useful to study synchronized cell cycle in vivo. Hepatic regeneration led to increased levels of anandamide and endocannabinoid‐like molecules oleoylethanolamide (OEA) and palmitoylethanolamide (PEA) in the G1 phase of the cell cycle, with a concomitant increase in CB1 mRNA levels, whose protein expression peaked later during the S phase. Blocking of CB1 receptor with a low dose of the selective antagonist/inverse agonist SR141716 (0.7 mg/kg/dose) affected cell cycle progression reducing the expression of PCNA, and through the inhibition of pERK and pSTAT3 pathways. These results support the notion that the signaling mediated by anandamide through CB1 receptor may be important for the entry and progression of cells into the cell cycle and hence for their proliferation under mitogenic signals. J. Cell. Physiol. 230: 2905–2914, 2015. © 2015 Wiley Periodicals, Inc.